New perspectives on land registration : contemporary problems and solutions - Dixon, Martin (Martin J.); Goymour, Amy; Watterson, Stephen, 1975- (Oxford [UK] ; Portland, Oregon : Hart Publishing, 2018)
The Land Registration Act 2002 has been in force for almost fifteen years. When enacted, the legislation, which replaced the Land Registration Act 1925, was intended to offer a clear and lasting framework for the registration of title to land in England and Wales. However, perhaps confounding the hopes of its drafters, the legislation's interpretation and application has since generated many unanticipated problems which demand attention. In this book's twenty chapters, leading land law scholars, Law Commissioners past and present, judges, and Registry lawyers unpick key technical controversies, and expose underlying theoretical and policy concerns. Core issues addressed in these chapters include: the legitimate ambitions of registration regimes; the nature and security of title afforded by registration; the resolution of priority disputes affecting registered titles; the relationship between the general law and the registration regime; and new challenges presented by modern technological developments
A (former) law reformer's perspective : reforming the LRA 2002 : catalysts and questions -- Elizabeth Cooke -- The land registry's perspective : the practical challenges of land registration -- John Pownall and Richard Hill -- The land registration jurisdiction : an analysis of the first twelve years -- Edward Cousins -- A broader development perspective: economic and political drivers of worldwide land registration reform -- Pamela O'Connor -- Adverse possession under the LRA 2002 -- Owen Rhys -- The continuing relevance of relativity of title under the Land Registration Act 2002 -- Amy Goymour and Robin Hickey -- Guaranteed title : no title guaranteed -- Emma Lees -- Can rectification be retrospective? -- Charles Harpum -- Assessing rectification and indemnity after Gold Harp and swift 1st -- Roger Smith -- De-throning King Midas : the new law of land registration in Scotland -- Kenneth GC Reid -- Lack of proper care? -- Simon Cooper -- Reforming the indemnity scheme -- Nicholas Hopkins -- Priority contests involving registered titles -- Martin Dixon -- Subrogation, priority disputes, and rectification : mapping a route through the thicket? -- Stephen Watterson -- A tale of three promises : setting the scene -- Stephen Watterson and Amy Goymour -- A tale of three promises : (1) the title promise -- Stephen Watterson and Amy Goymour -- A tale of three promises : (2) the priority promise -- Stephen Watterson and Amy Goymour -- A tale of three promises : (3) the empowerment promise -- Stephen Watterson and Amy Goymour -- Lessons from Scottish land registration reform : changes under the bonnet? -- Emma Waring -- Automating state guarantee of title systems : system design and possible outcomes? : Australasian thoughts -- Rod Thomas, Roushi Low, and Lynden Griggs.
Includes bibliographical references and index.
Also issued in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Electronic reproduction.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Great Britain; Great Britain; Land titles -- Registration and transfer -- Great Britain